LPSO: AN EFFICIENT ALGORITHM SCHEDULING OF SCIENTIFIC WORKFLOWS IN CLOUD COMPUTING - Toàn, Phan Thanh; Lộc, Nguyễn Thế; Cường, Nguyễn Doãn (Vietnam Journal of Science and Technology, 2016)
The key factor which rules the cloud’s performance is the workflow scheduling, one of the well-known problems have proven to be NP-complete. Many algorithms in the literature have been targeting the workflow scheduling problem, however, handful efficient solutions have been proposed. This paper proposes a metaheuristic algorithm called LPSO, which based on the Particle Swarm Optimization method. Our experiments, which arranged by using the simulation tool CloudSim show that LPSO is superior to the general algorithms called Random and  RoundRobin, moreover the deviation between the solution found by LPSO and the optimal solution is negligible.